Procrastination by pigeons: Preference for larger, more delayed work requirements - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1996)
In three experiments, pigeons chose between alternatives that required the completion of a small ratio schedule early in the trial or a larger ratio schedule later in the trial. Completion of the ratio requirement did not lead to an immediate reinforcer, but simply allowed the events of the trial to continue. In Experiment 1, the ratio requirements interrupted periods in which food was delivered on a variable-time schedule. In Experiments 2 and 3, each ratio requirement was preceded and followed by a delay, and only one reinforcer was delivered, at the end of each trial. Two of the experiments used an adjusting-ratio procedure in which the ratio requirement was increased and decreased over trials so as to estimate an indifference point-a ratio size at which the two alternatives were chosen about equally often. These experiments found clear evidence for `'procrastination”-the choice of a larger but more delayed response requirement. In some cases, subjects chose the more delayed ratio schedule even when it was larger than the more immediate alternative by a factor of four or more. The results suggest that as the delay to the start of a ratio requirement is increased, it has progressively less effect on choice behavior, in much the same way that delaying a positive reinforcer reduces it effect on choice.
Keywords: *Appetitive Behavior; *Conditioning, Operant; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Attention; Choice; Choice Behavior; Columbidae; Conditioning, Operant; Delay; Inhibition (Psychology); Inhibition, Psychological; Key peck; Motivation; Pigeons; Problem Solving; Procrastination; Ratio schedules; Reinforcement Schedule; animal; appetite; article; attention; decision making; dept.psy; inhibition (psychology); instrumental conditioning; motivation; pigeons and doves; problem solving; reinforcement